Challenges of Education and Employment of Young People: The Case of Kosovo - Loku, Afrim; Loku, Nadire (Asian Journal of Contemporary Education, 2022)
The goal of every young person not only in Kosovo but also beyond remains to find a job that would be safe and liked by them. The young years for all young people are rightly considered as one of the most important challenges, as each of these age groups is at the "crossroads" of a weighty decision for his / her future. This time consists of starting/completing the educational process and finding a job. If the young person completes the education cycle and is employed according to the qualification he has completed then this would have a positive impact not only on him but also on society in general. Many young people have difficulty finding a job after finishing school and some of them cannot do it at all or are forced to be a part of the "gray economy". This type of employment has a negative impact not only on workers but also on increasing informality in the country.